Diseño de instrumentos de evaluación aplicados al campo de cultura física en los décimos años de educación general básica en la unidad educativa Vicente León en el año 2014 – 2015 - Mena Alvarez, Jhonny Javier (2015)
The assessment tools are essential for assessing the teaching-learning process, for that reason, the need for research on the topic is created to improve evaluation processes in physical culture, the main object of study; the student. Since assessment instruments have a positive impact academically and intellectually; more than that these instruments can give an evaluation integrative approach, using them as useful tools in the process of teaching - and considering that the problem arose because of lack of information, of interest to promote and encourage proper evaluation in Physical Culture….